A novel concept for managing thermal interference between geothermal systems in cities. (January 2020) - Attard, Guillaume; Bayer, Peter; Rossier, Yvan; Blum, Philipp; Eisenlohr, Laurent
Abstract: The growing interest in shallow geothermal resources leads to dense installation areas, where interference and decrease in efficiency might occur. To optimize geothermal use in cities which prevents interference between neighbouring and future installations, we present a novel concept relying on the definition of thermal protection perimeters (TPP) around geothermal installations. These perimeters are determined by quantifying the thermal probability of capture around closed- and open-loop geothermal systems. Then, the maximal acceptable power that can be exploited in the vicinity of the installations can be continuously mapped. Existing analytical heat transport models are adapted to calculate these thermal capture probabilities. Two applications are illustrated in Lyon (France). The first application shows that adapted analytical models can help to manage multiple geothermal installations already in place in sectors of few square kilometres. In the second application, a numerical deterministic model is used to determine the TPP of one open-loop system at a local scale. The numerical approach applied for this case allows to account for flow disturbances caused by underground constructions, and thus offers a refined representativeness of the probability of capture. The presented methodology facilitates compatibility assessments between existing and planned new geothermal installations, which is otherwise not feasible by only mapping thermal plumes caused by existing installations, as done in common practice. Highlights: A novel methodology to manage multiple geothermal installations is presented. This methodology is based on the delineation of capture zones. Two analytical models are adapted to determine thermal probabilities of capture. A numerical model is used to apply the methodology in a densely built environment.